TEMPERATURE DISTRIBUTION IN MULTILAYER METAL-CERAMIC COATINGS UNDER NONSTATIONARY THERMAL EFFECTS - V. M. Samoilenko; Y. V. Petrov; O. A. Ratenko (Научный вестник МГТУ ГА)
Progress in the aircraft engine construction is determined by the increase of operation parameters of gas turbine engines, which is inevitably accompanied by an increase of operating temperatures and load for the vital elements of the turbine hot ducts. Furthermore, the requirements for reliability of the engine in general are also increasing. Achievement of these requirements is determined by the performance of the materials turbine blades are made of and is made possible by the application of high-heat Nickel alloys in combination with combined heat-shielding coatings.This article dwells on the problem of assessing the impact of non-stationary thermal effects on the temperature distribution in a multilayer heatproof coating. With the aim of assessing the working capacity of heatproof coatings we propose a method of calculating the temperature field for the blade profile and the coatingdepth, based on the solution of the basic one-dimensional differential equation of heat conduction.This method allows us to assess the performance of heatproof coating and also gives us an opportunity to choose a combination of heatproof coating layers for the specific operating conditions of a gas turbine engine’s blades.In addition, using the proposed method it is possible to evaluate the effect of non-stationary heat flux on the structure of high-temperature alloy of the engine’s turbine blades and, therefore, to evaluate the capacity with the given coating. At temperatures of 1150–1200 °C and higher in heat-resistant Nickel alloys there starts a coagulation process of the main reinforcing coherent particle phase on the basis of the intermetallic compound, long plates with wavy shapes are formed instead of the cuboids, a formation of topologically close-packed phases which are needle-like compositions happens. These processes lead to a significant deterioration of the strength characteristics of heat-resistant alloys. Making calculations according to the proposed method it is possible to predict the performance of turbine blades, having the information about the intensity of phase transformations in the alloy and the temperature transitions in the process of gas turbine engine functioning (using the data of the on-board parameters monitoring and recording systems).